PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT BERBANTUAN MEDIA RODA PUTAR TERHADAP HASIL BELAJAR IPAS KELAS V SDN 107400 BANDAR KHALIPAH - Tami Nopianti; Robenhart Tamba; Elvi Mailani; Suyit Ratno; Nurhudayah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This Study aimed to determine the effect of the NHT cooperative learning model assisted by spinning wheel media on IPAS learning outcomes in the topic of harmonious ecosystems among fifth garde students at SDN 107400 Bandar Khalipah. This study employed a quantitative experimental research method using a Pre-Experimental Design with a One-Group Pretest-posttest type. The population as well as the sample consisted of all 34 fifth grade students of SDN 107400 Bandar Khalipah. The sampling technique used was saturated sampling. Data were analyzed using SPSS Statistics 27 through hypothesis testing with a paired sample t-test. The result showed that the mean pretest score was 56.94 and the mean posttest score was 80.00. The hypothesis test result indicated that the significance value was 0.001 < 0.05, therefore H0 was rejected and Ha was accepted. Thus, it can be concluded that the NHT cooperative learning model assisted by spinning wheel media had a significant effect on the IPAS learning aoucomes of fifth grade students at SDN 107400 Bandar Khalipah.